Analisa Pengaruh Variasi Temperatur Tuang Pada Proses Pengecoran Alumunium Kaleng Bekas Terhadap Sifat Kekerasan Dan Struktur Mikro - Togubu, Sukirman A; Tjiroso, Bambang; Karim, Ivan Junaidy Abd (Department of Electrical Engineering, University of Patria Artha, 2024)
The purpose of this study is to determine the effect of casting temperature variations on the hardness and microstructure of used aluminium cans. The casting method used in this research is the Lost Foam Casting method with a cast temperature variation of 670°C, 700°C and 730°C. Vickers hardness testing was carried out to determine the effect of temperature variations on hardness, microstructure observations were made to see what phenomena occurred. The results show that the hardness value with the lowest temperature of 670°C has a higher average hardness value in the Vickers test compared to the high temperature of 730°C. This shows that the pouring temperature rate of metal castings is more effective in metal recycling at 670°C for the hardness value in the Vickers test. Porosity decreases with increasing pouring temperature, seen at 670°C with a microstructure magnification of 100x the porosity is rather round and large on the surface of the castings. While at a temperature of 730°C with a magnification of 100x microstructure, it can be seen that the porosity is getting smaller in the form of dots scattered on the surface of the castings.